2012
DOI: 10.1016/j.jtrangeo.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling transport and real-estate values interactions in urban systems

Abstract: a b s t r a c tThis article presents hedonic Multiple Linear Regression models (MLR), spatial autoregressive hedonic models (SAR), Spatial autoregressive hedonic in the Error term Models (SEMs) and spatial Durbin hedonic models (SDMs) to estimate house price variations in metropolitan areas as a result of changing environmental and accessibility conditions. The goodness of fit of the different models has been compared along with a series of hypotheses about the performance of the specifications considering spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 32 publications
1
65
1
3
Order By: Relevance
“…The TRAIN variable representing accessibility using suburban railway transport, presented a different sign parameter in agreement with previous research (Ibeas at al., 2012). This can be justified considering that railway infrastructures imply diseconomies related to noise and a lower landscaping and environmental quality in the city of Taranto, in this case had negative sign.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The TRAIN variable representing accessibility using suburban railway transport, presented a different sign parameter in agreement with previous research (Ibeas at al., 2012). This can be justified considering that railway infrastructures imply diseconomies related to noise and a lower landscaping and environmental quality in the city of Taranto, in this case had negative sign.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review of the various research work carried out can be found in Fujita (1989). The hedonic studies relating real estate prices with transport conditions have complemented the theories on urban economy and tested their hypotheses through multiple case studies (Ibeas and al., 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies adopt spatial econometric estimation to address the spatial dependence in hedonic modeling, but the spatial impact of transportation infrastructure does not seem to be quantified appropriately. For example, Ibeas et al (2012) adopted three spatial econometric models including a spatial autoregressive, a spatial error and a spatial Durbin to evaluate the impact of transport on real-estate value in the case of a Spanish metropolitan area. The impact of transport was measured by two dummy variables that indicate whether there is a bus stop or a suburban train station near a housing property.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Madrid, Dorantes et al (2011) concluded that a new metro line had positive impacts on house prices in south Madrid. In another case study, Ibéas et al (2012) found that, in Santander (Spain), proximity to http://dx.doi.org/10.1016/j.jtrangeo.2014.10.009 0966-6923/Ó 2014 Elsevier Ltd. All rights reserved. train stations drives house prices lower.…”
Section: Land-use and Transport Interactionmentioning
confidence: 99%